2023
DOI: 10.55133/eji.300111
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mutated citrullinated vimentin antibodies in rheumatoid arthritis; diagnostic utility and association with deformities and disease activity

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease with multiple morbidity burdens. Early diagnosis of RA is the main key in management and prevention of disease complications. Much research nowadays is looking for a serological marker with high accuracy in diagnosis of early RA cases. Our aim in this study was to evaluate the role of anti-mutated citrullinated vimentin (anti-MCV) antibodies in the early diagnosis of RA. In addition to compare its diagnostic sensitivity and specificity with anti-cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These results were consistent with another study [26], which found a sensitivity of 75.6% and specificity of 91.5% for MCV-Abs in RA patients. Similarly, Mohammed et al [28] reported that anti-MCV-Abs had a specificity of 83% and sensitivity of 63%. In another study, the anti-MCV-Abs test showed a good level of sensitivity (74%) and a higher level of specificity (96.1%) [29].…”
Section: Resultsmentioning
confidence: 91%
“…These results were consistent with another study [26], which found a sensitivity of 75.6% and specificity of 91.5% for MCV-Abs in RA patients. Similarly, Mohammed et al [28] reported that anti-MCV-Abs had a specificity of 83% and sensitivity of 63%. In another study, the anti-MCV-Abs test showed a good level of sensitivity (74%) and a higher level of specificity (96.1%) [29].…”
Section: Resultsmentioning
confidence: 91%
“…Vimentin citrullination results in a loss of vimentin’s normal functions but also triggers the production of anti-citrullinated protein antibodies (ACPAs) ( 60 ), which have been shown to induce osteoclastogenesis and bone loss ( 61 , 62 ). As a consequence, anti-citrullinated antibodies and more generally ACPAs represent a valuable diagnostic and prognostic marker of rheumatoid arthritis ( 63 , 64 ).…”
Section: Vimentin Structurementioning
confidence: 99%